From Complexity to Prosperity: Economic Complexity’s Impact on BRICS Economic Wealth - Öcal, Kayhan; Küçükkocaoğlu, Güray (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026, 2026)
This study examines the impact of technological advancement on economic wealth in BRICS countries over the period 2000–2020. Technological advancement is measured using the Economic Complexity Index (ECI). Economic wealth is measured using a revised Economic Wealth Index (EWI), constructed by excluding GDP, patent applications, and the ECI.Short-run effects are estimated using a panel fixed effects model with Driscoll–Kraay robust standard errors. Long-run relationships are examined through Pedroni cointegration tests and Panel Dynamic Ordinary Least Squares (PDOLS) analysis. Analyses indicate that ECI has a positive and statistically significant effect (p<0.01) on EWI in both the short and long run. According to the test results, a one-unit increase in ECI leads to an increase of approximately 1.49 units in EWI in the short term and 1.82 units in the long term. These findings suggest that the level of advanced technology and investments in research and development plays an important role in increasing economic wealth. This study differs from previous studies in the literature by examining both the short- and long-run effects of technological advancement on economic wealth using a revised EWI.